Christmas child [videorecording (DVD)] - Ewing, Bill; Moses, William R.; Follows, Megan; Watson, Muse, 1948-; Lucado, Max (Bridgestone Multimedia Group, 2010)
As Christmas draws near, Jack finds himself disconnecting from the holidays, his job, and ultimately his wife. His latest assignment as a journalist takes him to Dallas, but a mysterious photograph draws him to the town of Clearwater, Texas. It is here he discovers the town's life-sized, intricately carved nativity. As Jack delves into the mysteries surrounding the nativity and its creator, he uncovers secrets from his past, reunites with the family he never knew, and returns to the love that never left him--Container.